Publication Trends of Journal Articles about Religious Moderation in Recent Years: Bibliometric Analysis - Eko Harianto (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
In recent years, religious moderation has piqued the interest of Indonesian experts. This research aims to conduct a bibliometric examination of multiple scientific generations over the last few years. The Scopus database was searched for publications, and six results were analysed with BibExcel software and visualised in VOSviewer. English is the principal language of publication. The year 2021 will see the most publications on religious moderation. As a result, a systematic review and meta-analysis of the content of the identified papers and the variables connected with this topic are required. It can serve as a starting point for future study in this field and a foundation for future reviews of its evolution and advancement.